The role of O-GlcNAcylation in bone metabolic diseases - Yang, Yajing; Zhou, Xuchang; Deng, HuiLi; Chen, Li; Zhang, Xiaolin; Wu, Song; Song, Aiqun; Liang, Fengxia (Frontiers in Physiology, 2024)
O-GlcNAcylation, as a post-translational modification, can modulate cellular activities such as kinase activity, transcription-translation, protein degradation, and insulin signaling by affecting the function of the protein substrate, including cellular localization of proteins, protein stability, and protein/protein interactions. Accumulating evidence suggests that dysregulation of O-GlcNAcylation is associated with disease progression such as cancer, neurodegeneration, and diabetes. Recent studies suggest that O-GlcNAcylation is also involved in the regulation of osteoblast, osteoclast and chondrocyte differentiation, which is closely related to the initiation and development of bone metabolic diseases such as osteoporosis, arthritis and osteosarcoma. However, the potential mechanisms by which O-GlcNAcylation regulates bone metabolism are not fully understood. In this paper, the literature related to the regulation of bone metabolism by O-GlcNAcylation was summarized to provide new potential therapeutic strategies for the treatment of orthopedic diseases such as arthritis and osteoporosis.